(3JbfjGJ JSjjQ ejRGfjGJ GdeDSSI GdEbJUGOjI GdeSJbdIs - (3NGdU GdUGaj(B, (3UGdMs ((3GdLRGFQ(B:s (3OjhGf GdeWHhYGJ GdLGeYjI(B,s, 2006)
(3fXGe GdejRGfjGJ GdJbOjQjI heSJdReGJ JWHjbjI(B- (3ELQGAGJ EYOGO GdejRGfjGJ GdJbOjQjI hCfhGY GdejRGfjGJ (B-(3GdejRGfjI GdJbOjQjI ddeHjYGJ(B- (3GdejRGfjI GdJbOjQjI GdEfJGL(B- (3GdejRGfjI GdJbOjQjI GdehGO GdChdjI(B- (3GdejRGfjI GdJbOjQjI ddYed HGdCLhQ(B- (3GdejRGfjI GdJbOjQjI ddeUGQa GdUfGYjI ZjQ GdeHGTQI(B- (3GdejRGfjI GdJbOjQjI ddeUGQja GdHjY hGdJhRjY(B- (3GdejRGfjI GdJbOjQjI ddJOabGJ GdfbOjI(B.s
Keywords: (3GdeDSSI GdEbJUGOjIs; (3GdejRGfjIs; (3JSjjQ GdeDSSIs